Implementasi Logika Fuzzy Inferensi Tsukamoto Pada Preventive dan Predictive Maintenance Sluge Separator Berbasis Smart Meter - Sunanto Sunanto; Reny Medikawati Taufiq; Rahmat Febri (Unversitas Muhammadiyah Riau, 2023)
The clarifier station is also known as a purification station. Its main function is to obtain palm oil in a very pure condition. There are several machines ready to work to refine Crude Palm Oil from palm oil. One of the machines at the refining station is the Sludge Separator which has the function of extracting oil that is still contained in a centrifugal manner where water and NOS with a specific gravity greater than oil will be thrown out and oil will enter the interior. The Sludge Separator method separates oil from water and NOS, namely by rotating (spinning) the bowl that has been installed and released through the nozzle. This rotation is generated from the conveyor motor. To optimize the work of the clarification station, especially on the Sludge Separator machine, a tool and system was created to monitor traffic flow, record the start time of the active Sludge Separator conveyor motor and schedule Preventive and Predictive Maintenance according to the working conditions of the motor, to make the system use the method/algorithm Fuzzy Tsukamoto. And in this research implementation, testing and results will be carried out on a prototype that utilizes the NodeMCU microcontroller (esp32), current and web sensors using hypertext preprocessor